Strengthening The Psychological Capital of The Former Shiite Community - Hanik Yuni Alfiyah; Muhammad Fahmi; Ali Mas’ud; Syaifuddin Syaifuddin (Communautaire: Journal of Community Service, 2025)
This community engagement project aims to strengthening of psychological capital in supporting the psychosocial readiness of former Shia residents of Jemundo prior to their return to Sampang Regency in a post-religious conflict context. Psychological capital—comprising hope, optimism, self-efficacy, and resilience—is understood as an integrated construct that plays a crucial role in enabling individuals to navigate social transitions characterized by uncertainty. The program was implemented through a participatory approach that positioned community members as active subjects in the psychosocial accompaniment process. The findings indicate that the four dimensions of psychological capital mutually reinforce one another and contribute to participants’ capacity to reconstruct the meaning of return in a more adaptive manner. Nevertheless, the development of psychological capital cannot be detached from the structural conditions shaping post-conflict experiences, including state policies and local social relations. Therefore, strengthening psychological capital should be framed as complementary to, rather than a substitute for, the state’s responsibility to ensure the fulfillment of citizens’ basic rights. This study recommends the integration of psychosocial interventions and responsive structural policies to support sustainable social reintegration.